Comprehensive Cloning of Prunus mume Dormancy Associated MADS-Box Genes and Their Response in Flower Bud Development and Dormancy - Zhao, Kai; Zhou, Yuzhen; Ahmad, Sagheer; Xu, Zongda; Li, Yushu; Yang, Weiru; Cheng, Tangren; Wang, Jia; Zhang, Qixiang (Frontiers in Plant Science, 2018)
Dormancy Associated MADS-box genes are SVP/MADs-box members and supposed to play crucial roles in plant dormancy of perennial species. In Prunus mume, PmDAM6 has been previously identified to induce plant dormancy. In the current study, six PmDAMs were cloned in P. mume and functionally analyzed in yeast and tobacco to detect the roles of the genes paralogous to PmDAM6. The expression patterns together with sequence similarities indicate that PmDAMs are divided into two sub-clades within SVP group. Moreover, PmDAMs are verified to take part in the development of different plant organs, specifically the flower buds, in some intricate patterns. Furthermore, the PmDAM proteins are found to have special functions by forming corresponding protein complex during the development of flower bud and induction of dormancy. In particular, when PmDAM1 dominating in flower bud in the warm months, the protein complexes are consisted of PmDAM1 itself or with PmDAM2. With the decrease temperatures in the following months, PmDAM6 was found to be highly expressed and gradually changed the complex structure to PmDAM6-protein complex due to strong binding tendencies with PmDAM1 and PmDAM3. Finally, the homodimers of PmDAM6 prevailed to induce the dormancy. The results obtained in the current study highlight the functions of PmDAMs in the tissue development and dormancy, which provide available suggestions for further explorations of protein-complex functions in association with bud growth and dormancy